2015
DOI: 10.1136/bcr-2015-211560
|View full text |Cite
|
Sign up to set email alerts
|

Combined pulmonary fibrosis and emphysema in hypersensitivity pneumonitis

Abstract: SUMMARYCombined pulmonary fibrosis and emphysema is a distinct syndrome reported in patients who smoke. A 72-year-old, never-smoking female dairy farmer was referred for progressive dyspnoea on exertion, basal crackles on auscultation, normal spirometry and normal lung volumes but decreased diffusing capacity of the lung for carbon monoxide, centrilobular emphysema in the upper zones of the lungs and diffuse infiltrative lung disease in the lower zones on high-resolution CT scan. Bronchoalveolar lavage differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…Long-term exposure can lead to pulmonary fibrosis, respiratory failure, pulmonary hypertension, and pulmonary heart disease [12]. Xinjiang is an area with multi-ethnic inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure can lead to pulmonary fibrosis, respiratory failure, pulmonary hypertension, and pulmonary heart disease [12]. Xinjiang is an area with multi-ethnic inhabitants.…”
Section: Discussionmentioning
confidence: 99%
“…É um importante fitopatógeno, sendo muito prejudicial para as culturas vegetais . Para os seres humanos e animais, nem todas as cepas são patogênicas, entretanto algumas cepas podem provocar ocasionalmente feo-hifomicose cutânea e cerebral independentemente do estado imunitário do hospedeiro (Soumagne et al, 2015;Maduri et al, 2015).…”
Section: Principais Espécies Patogênicasunclassified
“…Several recent studies have also identified the presence of emphysema on CT imaging in never-smoker patients with rheumatoid arthritis-related ILD (RA-ILD) [ 8 , 9 ], scleroderma-related ILD [ 10 ] and IPF [11 ]. Reports also suggest that emphysema occurs in never-smoker patients with HP [ [12] , [13] , [14] ]. Our study therefore aimed to characterize the prevalence and functional and prognostic effects of emphysema and PPFE identified on CT imaging in a large population of patients with hypersensitivity pneumonitis.…”
Section: Introductionmentioning
confidence: 99%